Analisis Peluang dan Tantangan PSI Pasca Pemilu 2024: Peluang Jokowi menjadi Ketua Umum PSI - Adhitya Hafizh Rasyadi; Sagitha Dwi Herliany; Syallika Nurussyahadah; Taqya Mafaza; Abdul Ghofur (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This study analyzes the political implications of the discourse on President Joko Widodo's (Jokowi) involvement in the leadership of the Indonesian Solidarity Party (PSI) after the 2024 Election, and examines the internal and external challenges that the party may face. The main focus of this study is to understand how Jokowi's figure, with his populist leadership style and strong political track record, can influence the structure, culture, and image of PSI in the eyes of the public. The method used in this study is descriptive qualitative with a case study approach. Data were collected through in-depth interviews with informants who have a political background, as well as analysis of relevant literature and media. Data analysis techniques were carried out thematically to identify narrative patterns regarding the opportunities and challenges of Jokowi's involvement in PSI. The results of the study show that Jokowi's presence in PSI can be a catalyst in expanding the party's electoral reach, especially through a more down-to-earth and pro-people political approach. However, this involvement also raises a number of serious challenges. Internally, there is the potential for ideological change, to the restructuring of the party's organizational culture. While externally, there is resistance from the public regarding the issue of dynasty politics and concerns over the loss of PSI's idealistic identity. In addition, pressure from other political parties is also an external factor that needs to be anticipated. This finding shows that although Jokowi's presence has the potential to strengthen PSI, an adaptive strategy is needed so that the party remains relevant and credible in the eyes of voters